ANALISIS PRODUKTIVITAS PEKERJA DALAM PEKERJAAN PEMASANGAN BATA RINGAN PADA PROYEK PEMBANGUNAN GEDUNG SERBAGUNA POLRES DAN REHABILITASI RUANG KAPOLRES KOTA BANJARBARU - Putri, Tania Ananda Tasia Hariyanto; Cahyadi, Hendra; Rachman, Tezar Aulia (INFO-TEKNIK, 2023)
In the world of construction services, labor productivity is one of the determining factors for the success of a development project. In measuring the level of labor productivity there are various ways, one of which is by direct observation in the field by looking at the work of each worker. The purpose of this study was to determine the coefficient/index value of the workers in the brick wall laying work cycle in the Polres Multipurpose Building Development project and the Kapolres Room Rehabilitation project in Banjarbaru City and to determine the coefficient comparison of bricklaying workers in the POLRES Multipurpose Building Construction project and Spatial Rehabilitation The Banjarbaru City Police Chief when compared with the 2022 Work Unit Price Analysis (AHSP). This research was conducted by observing the productivity level of 4 light brick laying workers. From the data analysis that has been done, it can be seen that the coefficient or index of masons on the work of laying red brick walls on the construction project of the Banjarbaru Police Multipurpose Building and Kapolres Room Rehabilitation has an average of 0.064 OH. Meanwhile, the coefficient or masonry index according to Minister of Public Housing and Public Housing Regulation No. 1 of 2022 is 0.13 OH. This means that the coefficient or index value of the carpenter's data from the field is smaller in value compared to the coefficient or index in Regulation of the Minister of Public Affairs and Public Housing No. 1 of 2022. The percentage comparison of the coefficient or index of the masonry is obtained 0.066.